Os espaços de formação e a constituição da profissionalidade docente: o estágio e o ensino de Matemática nos anos iniciais do Ensino Fundamental - Marquesin, Denise Filomena Bagne (2012)
The focus of this research fits in the discussions of teacher formation, emphasizing the Supervised Stage on Pedagogy and the teaching of Mathematics in the early years of elementary school. The understanding that much professional knowledge resulting from the student´s participation on the Supervised Stage, was crucial to perform this research. The overall aim of this study was to evaluate how the areas become places of training and learning of teaching, as well as verify how this areas/places influence in the in the formation of teaching prowess and obtaining of knowledge to teach mathematics. As theoretical-methodological referential in the fields of professional knowledge and teaching learning, were used contributions from Montero (2001), Shulman (1987), Roland (2005, 2006), Gauthier (1998) and Nóvoa (1995). For the discussion of training areas, the study bolstered in Escolano (2000), Viñao_Frago (2001) and Cunha (2010). The study was also relied on Pires (2000) and Moura (2001) for issues related to teaching mathematics in the early years of elementary school. This is a qualitative research based on a case study. As data collection, was used an initial questionnaire, exploratory interview, discussion and narratives group. In this way, we started with the assumption that the stage can influence the formation of the teaching; and the discussion meetings allow the student of the Pedagogy to think about the professional content to teach and to ensure learning. The analysis indicates that the students of the Supervised Stage, when insert themselves in the school and participate in class, has a possibility to establish the relationship between theoretical knowledge and knowledge of content and teaching. The reflection on this process revealed that the meanings and achievements make the school a place of learning and bring peculiarities to teaching prowess